Peletizacion de semillas de soya y su interaccion con el uso de inoculantes y de nitrogeno - Castro F., H.E.
(Es, En)
ilus., 10 ref.
Keywords: GLYCINE MAX; PILDORACION DE SEMILLAS; BRADYRHIZOBIUM JAPONICUM; INOCULACION; NITROGENO; SUELO; PRODUCCION; COLOMBIA